Globalization and Reorientation of Pesantren Education - Irwan Satria (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2021)
Islamic boarding schools are one of the important pillars in the world of education, therefore they are called the oldest educational institutions in Indonesia. The roles and contributions given to society are numerous. Among them as a place for learning, a place for discussion and so on. Not only religious lessons but even general lessons are given by pesantren today. So it cannot be denied that there are many great people who were born from Islamic boarding schools. In facing the era of globalization, pesantren still exist with their Islamic traditional values. At this time it has been seen that many pesantren have not only implemented the typical pesantren learning system, namely the sorogan, wetonan, and bandongan systems, but learning through formal schools is also provided at the pesantren. Various kinds of formal education are given starting from kindergarten to college though. To see this phenomenon, this study uses qualitative data with phenomenological theory. Pesantren will continue to exist if they adopt changes without having to lose their identity. The challenge of facing the current of globalization which is increasingly growing, pesantren persistently maintains the side of the social tradition of education, even though the pesantren side reduces the government education system. This happens because pesantren want to create new innovations, besides that, because pesantren try to eliminate the thinking of the people who think that pesantren are educational institutions that are still traditional and conservative because they miss information from the outside world. Therefore, taking steps in adopting education systems and patterns from outside is the right step for pesantren which has such problems.